Penguasaan tatabahasa Melayu dalam kalangan pelajar di Universiti Teknologi Malaysia - Mohamad Nasir, Zaliza; Zainon Hamzah, Zaitul Azma; Sheikh Said, Normahdiah; Che Su, Norizan (Persatuan Linguistik Malaysia, 2013)
This descriptive research was carried out to identify the mastery of Malay language proficiency level among foreign students of Universiti Teknologi Malaysia. As many as 14 students had been chosen as research sample. The research instruments used in this study was questionnaire which consists of 53 items. All the data collected were being analysed by using computer with Statistical Packages for Social Science (SPSS) Version 15.0 to determine the value of frequency and percentage. Research showed that the skill level of writing and speaking among students are moderate if they could get tutoring from their instructor. On the other hand, using a dictionary is one of the main factors in using the correct grammar and editional vocabullary. The findings also suggest that environmental factors and peers group also influencing students’ in mastering basic grammar in bahasa Melayu. In conclusion, the mastery of Malay language proficiency level among students is moderate.